Composition and yield of milk from non-dairy goats and sheep in Malawi - Banda, J.W.; Steinbach, J.; Zerfas, H.P. (International Livestock Centre for Africa, 1992)
Milk yield, milk composition and growth rates of offspring from goats (local-LL, Boer-BB and their crosses-Be) and of sheep (local-LL, Dorper-DD and their crosses-De) were estimated over two kidding/lambing seasons for 12 weeks of lactation using three techniques of milk-yield estimation, namely kid/lamb suckling, hand-milking and oxytocin + hand-milking.Mean total milk production in the dry end wet seasons was 84.6±3.1, and 66.8 ± 2.6kg, respectively, for goats; 50.2 ± 1.7 and 49.3 ± 1.9 kg, respectively, for sheep. Only the seasonal difference in goats was significant (P<0.001). Estimates of milk yield by stickling and oxytocin techniques were similar. Handmilking produced 26.8% and 40.5% less milk than the other two techniques in goats and sheep, respectively. The yields of LL (70.6 ±2.5 kg) and BB (75.0 ±3.8 kg) were similar, but significantly lower (P < 0.001) than those of BL does (81.6 ±2.3 kg). Local, DL and DD ewes produced, respectively, 37.8±1.8, 48.9±1.6 and 62.7±2.1 kg milk end the differences among these genotypes were significant (P<0.001). Dorper ewes did not perform as well in the rainy season as they did in the dry season.The overall mean levels of total solids, fat, SNF,, ash, protein, lactose and energy for goats were 17.4%, 6.8%, 10.6%, 0.88%, 4.5%, 4.7%, and 4.44 MJ/kg, respectively. The respective values for sheep were 18.3%, 6.0%, 12.3%, 0.94%, 5.2%, 4.9% and 4.39 MJ/kg. Within each species, significant differences in compositional values between seasons, among techniques of milk-yield estimation and among genotypes were observed and are discussed.Overall birth, weaning weight at 17 weeks and pre-weaning daily liveweight gains for kids were 2.77±0.08 kg, 13.0± 0.41 kg and 87.0±3.5 g, respectively. The values of sheep were, respectively, -3.19± 0.05 kg, 18.5±0.32 kg and 128.9 ±2.5 g. In goats, season of kidding had significant effect on all these traits, but genotype had effect only on kid birthweight. In sheep, season and genotype exerted significant influences in all the lamb traits. Correlations between milk yield and growth rate of the young were significantly high and positive Regressions of growth rate on milk production for kids were poorer than those for lambs.